A Comparative Study of Four Feedback Linearization Schemes for Motion Planning of Fixed-Wing Unmanned Aerial Vehicles - Khamseh,Hossein Bonyan (2016)
ABSTRACT In this paper, different feedback linearization schemes are studied to address the motion planning problem of fixed-wing unmanned aerial vehicles. For a unmanned aerial vehicle model with second-order dynamics, several schemes are studied to make the vehicle (i) fly over and (ii) make a loitering around the objective position. For each scheme, comparisons are made to illustrate the advantages and disadvantages. Lyapunov stability analysis is used to prove the stability of the proposed schemes, and simulation results for some case studies are included to show their feasibility.